2023
DOI: 10.3390/ijerph20126103
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Media Affect a Patient’s Decision to Undergo Orthognathic Surgery?

Omar Alsuhaym,
Ibrahim Aldawas,
Fahad Maki
et al.

Abstract: Orthognathic surgery, also known as corrective jaw surgery, is a procedure that corrects abnormalities of the jaw and face. It is used to treat malocclusions, where the teeth and jaws are misaligned. This surgery can improve the function and appearance of the jaw and face, leading to improved mastication, speech, and quality of life for the patients. To assess if social media had any effect on the patients’ decision to undergo orthognathic surgery, a self-administered online questionnaire was distributed to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…At the same time, patients awaiting surgery often wish to hear first-hand, the experiences of others and SoMe can allow for this. In a survey of patients undergoing maxillofacial surgery, it was found that SoMe can influence decision to undergo surgery as well as by which medical provider ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, patients awaiting surgery often wish to hear first-hand, the experiences of others and SoMe can allow for this. In a survey of patients undergoing maxillofacial surgery, it was found that SoMe can influence decision to undergo surgery as well as by which medical provider ( 8 ).…”
Section: Introductionmentioning
confidence: 99%